2004
DOI: 10.1007/s00421-004-1044-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different inspiratory muscle training intensities on exercising heart rate and perceived exertion

Abstract: This study investigated the relationship between the intensity of an inspiratory muscle training programme and its effect on respiratory muscle strength, exercising heart rate, and ratings of perceived exertion. A total of 66 subjects were randomly assigned to one of three groups. One group trained at 100% of maximum inspiratory pressure (MIP) for 6 weeks (MAX, n=22). A second group performed 6 weeks of inspiratory muscle training at 80% of MIP (SUB, n=21) and a third control group received no inspiratory trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 33 publications
4
26
2
2
Order By: Relevance
“…By the end of the 10 week intervention, the EMT group achieved an improvement of 13% in P Imax , with no associated change in rowing performance; Hart et al (2001) also observed no change in incremental treadmill performance after a 6 week program of IMT that increased P Imax by 10%. This suggests that improvement in performance following IMT requires an intensity of training that increases P Imax by >25% (Volianitis et al 2001b;Romer et al 2002a, b;Edwards and Cooke 2004;Gething et al 2004a, b). A further contributory factor to the poorer than anticipated strength improvements during the combined training phase may have been the training device.…”
Section: Inspiratory Muscle Strengthmentioning
confidence: 90%
See 2 more Smart Citations
“…By the end of the 10 week intervention, the EMT group achieved an improvement of 13% in P Imax , with no associated change in rowing performance; Hart et al (2001) also observed no change in incremental treadmill performance after a 6 week program of IMT that increased P Imax by 10%. This suggests that improvement in performance following IMT requires an intensity of training that increases P Imax by >25% (Volianitis et al 2001b;Romer et al 2002a, b;Edwards and Cooke 2004;Gething et al 2004a, b). A further contributory factor to the poorer than anticipated strength improvements during the combined training phase may have been the training device.…”
Section: Inspiratory Muscle Strengthmentioning
confidence: 90%
“…IMT reduces HR at equivalent intensities of exercise (Haas and Haas 1981;Swanson 1998;Gething et al 2004a), as well as reducing [La -] B , respiratory and/or whole body effort sensations (Volianitis et al 2001b;Romer et al 2002a, b). Gething et al (2004a) observed a decrease in exercising HR of~6 bpm at the end of a 5 min bout of constant power cycling after their 6 week of IMT that increased P Imax by 29%.…”
Section: Physiological Variablesmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding is supported by Granados et al (2016), who observed that individuals who wore the ETM-like mask had significantly higher RPE throughout a 30-minute treadmill exercise session. Additionally, Gething et al (2004) found that after 6 weeks of IMT at 100% of MIP, RPE was significantly decreased. It was suggested that IMT may provide an improvement in physiological conditioning that produces a reduction in perceived cost of breathing.…”
Section: Discussionmentioning
confidence: 96%
“…Inspiratory muscle training in athletes results in lower levels of dyspnoea (Bailey et al, 2010, Gething et al, 2004a, Kilding et al, 2010 and more specifically in a reduced estimation of the magnitude of a respiratory load (Kellerman et al, 2000). These findings further indicate that inspiratory muscle training's effect on dyspnoea may be a critical determinant of exercise performance success in athletes.…”
Section: The Effects Of Inspiratory Muscle Training In Athletes and Hmentioning
confidence: 52%